Analysis Of Landslide Susceptibility In The Cugenang New Fault Area In The North Of Cianjur Regency - Hermawan Setiawan; Adi Wibowo (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
A landslide is a disaster that often occurs in Indonesia, especially in morphology that has rough topography. This disaster is caused by faults, natural factors such as rainfall, topography, soil type, rock type, and human activity factors such as changes in land covered by a land cover or other factors related to landslide triggers. This research is located in the northern part of the Cianjur residency, this area is located between active volcanic mountains which have a distribution of sedimentary rocks and volcanic rocks, which are included in the Bandung physiographic zone, and have the new Cugenang fault. The unit of analysis is districts, which consist of 10 sub-districts. The purpose of this study was to analyze the landslide hazard distribution in the northern part of the Cianjur regency. The study used a sptial approach by using the weight overlay method for all parameters that have previously been analyzed and interpolated. The results of this study are very high Susceptibility covering 0.06%, high Susceptibility 47.49%, moderate Susceptibility 52%, and low Susceptibility 0.01%. The most vulnerable area is Sukaresmi, and the sub-district with moderate Susceptibility is Cikalong Kulon, while the low and high Susceptibility is relatively scattered in all areas with a small percentage. Based on the parameters analyzed, it means that rainfall and slope are the dominant driving factors in landslide Susceptibility in the northern part of the Cianjur regency because they have a large weight. This study provides a classification related to landslide susceptibility mapping in the northern part of Cianjur.